PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF IBNU SINA DAN RELEVANSINYA DI ERA MODERN - Ida Faridatul Hasanah; Uswatun Hasanah; Asma dewi (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2023)
Abstact: Islamic education faces problems not only in aspects of ideology, politics, finance and other problems, but also the arrival of the era of globalization, namely the industrial revolution 4.0 and society 5.0 which is a real movement towards the development of increasingly sophisticated information and technology. In response to the above problems, there have been many figures in various parts of the Islamic world who have had an influence on the progress of science. One of the figures in the Islamic world is Ibn Sina who is a Muslim scientist who has expertise in various fields .This study aims to examine Ibn Sina's thoughts on Islamic education and its relevance to education in the modern era. This research is a descriptive qualitative research, the type of research is library research with documentation data collection and content analysis methods. The results of this study indicate that Ibn Sina's Islamic Education thought seeks to form insan kamil, namely human beings who develop all their potential in a balanced and comprehensive manner. Ibn Sina's perspective of Islamic education is still relevant, even though the idea of education was not born in the modern era. This is based on the values of Islamic teachings that are sourced from the Qur'an and Sunnah. Thus, Ibn Sina's educational thoughts can certainly be taken into consideration in the implementation of education.Keywords: Islamic Education; Ibn Sina; Relevance